Design Thinking and Digital Marketing Skills in Marketing Education: A Module on Building Mobile Applications. Issue 3 (2nd September 2018) - Schiele, Kristen; Chen, Steven
Abstract : The purpose of this article is to demonstrate how marketing educators can utilize the design-thinking process to create an engaged, high-impact learning experience for students. The guidelines of the assignment outlined in this article show how marketing students can utilize the design-thinking process in order to create a mobile application that meet the needs of target consumers. This adaptable assignment was tested in two types of marketing courses, and findings indicate that students improved in the areas of empathy, creativity, communication skills, technology skills, critical thinking, and collaboration.